Implementasi Layanan Pendidikan Gratis di Provinsi Gorontalo: (Studi Evaluatif Kebijakan Peraturan Daerah No. 7 Tahun 2012 Tentang Penyelenggaraan Program Pendidikan untuk Rakyat) - Entengo, Adnan; G. Otaya, Lian; Asiah T., Siti (Al-Minhaj : Jurnal Pendidikan Islam, 2020)
In order to fulfill the people's education rights, Gorontalo government provide free education programs. The purpose of this research is to describe and analyze the implementation with a measured evaluation of the implementation of the Free Education Program named “PRODIRA”, that it contributes well to improving quality education services and can be useful for local governments and education stakeholders. The type of research used is descriptive evaluation research, while using data collection techniques; observation, interviews, documentation, data analysis techniques through the stages of data reduction, data presentation and drawing conclusions in the field with the Logi evaluation model. The results of the research are: (1) Implementation of education programs for the people in 2012-2016 and 2017-2019 has been running according to the relevant regional regulations, accompanied by a large budget allocation. However, it was found that the number of school dropout rate was high at junior and senior high school levels, and the program was still used for political interests. (2) Supporting factors and implementation issues found that there was a legal basis, budget allocation and formulation of free education policies. As a recommendation, a comprehensive study, input, process to the outcome of “PRODIRA” and coordination between the governor and the regent / mayor are needed in managing this policy both on legal basis and budget management in generating school with equal quality.